2020
DOI: 10.29333/iji.2020.13148a
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on Improving Reading Fluency at a University in the UAE

Abstract: Students native to the Arabian Gulf region often struggle with reading skills. The purpose of this study was to explore the reading habits and reading culture of Emirati undergraduate students and to investigate the use of a particular reading strategy (Listening While Reading) on undergraduate Emirati students reading rate and comprehension. This case study was conducted through a mixed method research design. It was carried out with sixty-one SLL (second language learners) undergraduate students. By assignin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
10
0
2
Order By: Relevance
“…Most previous studies, however, focused on mind mapping in general, with little research into the use of visual mind mapping strategies to improve undergraduate students' critical thinking skills and reading ability in the UAE. It has also been observed that Emirati undergraduate students struggle with reading skills (Eppard et al, 2020). Because of the facts stated above, critical thinking may be regarded as a necessary component contributing to students' success in learning English skills.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies, however, focused on mind mapping in general, with little research into the use of visual mind mapping strategies to improve undergraduate students' critical thinking skills and reading ability in the UAE. It has also been observed that Emirati undergraduate students struggle with reading skills (Eppard et al, 2020). Because of the facts stated above, critical thinking may be regarded as a necessary component contributing to students' success in learning English skills.…”
Section: Introductionmentioning
confidence: 99%
“…A similar result was found in the line of researches by (Kim & Wagner, 2011& 2015. On the contrary, the study by Eppard et al (2020) indicated that LWR improved students' reading fluency, accuracy, and rate but it did not develop reading comprehension.…”
Section: Discussionmentioning
confidence: 89%
“…Studies investigated the effectiveness of LWR and RR on learner's reading fluency (e.g., Blonder et al, 2019;Eppard, Baroudi, & Rochdi, 2020;Friedland, Gilman, Johnson, & Demeke, 2017;Hawkins, Marsicano, Schmitt, McCallum, Musti-Rao, 2015;Winn et al, 2006). Results affirmed that RR and LWR are two significant techniques that develop learners' reading fluency and comprehension.…”
Section: Repeated Reading (Rr) and Listening While-reading (Lwr)mentioning
confidence: 93%
“…Solo dos de los estudios contemplaron el uso de las tecnologías de la información y comunicación (Eppard et al, 2020;Ricciardi y Di Nocerab, 2017). Era esperable encontrar mayor uso de aplicaciones digitales tales como Reading A-Z (LAZEL, 2022), para realizar este tipo de investigaciones; no obstante, pocos documentos analizados las tomaron en cuenta y los casos que se emplearon, se requiere el pago para su uso óptimo, lo que puede explicar su poca utilización.…”
Section: Método Empleadounclassified